Good Research Practice in Non-Clinical Pharmacology and Biomedicine - Bespalov, Anton; Michel, Martin C.; Steckler, Thomas (Handbook of Experimental Pharmacology, 2020)
This open access book, published under a CC BY 4.0 license in the Pubmed indexed book series Handbook of Experimental Pharmacology, provides up-to-date information on best practice to improve experimental design and quality of research in non-clinical pharmacology and biomedicine.